Sulfur-containing palladacycles: Efficient phosphine-free catalyst precursors for the Suzuki cross-coupling reaction at room temperature - Zim, Danilo; Gruber, Adriane S. [UNESP]; Ebeling, Gunter; Dupont, Jairton; Monteiro, Adriano L. (American Chemical Society (ACS), 2000)
Cyclopalladated compounds derived from the ortho-metalation of benzylic tert-butyl thioethers are excellent catalyst precursors for the Suzuki cross-coupling reaction of aryl bromides and chlorides with phenylboronic acid under mild reaction conditions. A broad range of substrates and functional groups are tolerated in this protocol, and highly catalytic activity is attained.